Haematological Alterations In Bitches Affected With Pyometra - Gupta , A.K.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Haematological parameters were evaluated in nine pyometric and eight healthy bitches before and after ovario-hysterectomy. Significantly lower pre-operative mean haemoglobin (Hb) and total erythrocyte count (TEC) was found in pyometric bitches (11.22±0.83 g % and 5.76± 0.33 million/ cmm) than in healthy bitches (14.90±0.34 g % and 7.80±0.18 million/cmm). The mean pre-operative PCV value was significantly (P<0.01) lower (35.14±2.10 vs 42.02±0.88 %) and that of ESR was higher (10.36±1.48 vs 2.74±0.22 mm/hr) in pyometric bitches as compared to healthy ones. There was slight improvement in the Hb and TEC, and significant (P < 0.01) improvement in ESR post operatively, but not in PCV, in pyometric bitches. The mean pre-operative total platelet count (TPC) was significantly (P<0.01) lower in pyometric bitches than in normal healthy bitches (212.67±18.94 vs 421.00±26.62 thousand/cmm) and it improved significantly after ovario-hysterectomy. Pyometric bitches showed a significant (P< 0.01) leukocytosis as compared to healthy ones (31.98 ± 4.80 vs 14.79 ± 0.68 thousand/cmm). Neutrophil count was significantly (P < 0.01) higher (76.84 ± 1.96 vs 64.40 ± 2.12 %) and lymphocyte count was lower (18.83 ± 1.30 vs 32.93 ± 1.30 %) in pyometric bitches than the normal ones. The post-operative TLC and DLC counts shifted towards normalcy. The Hb, TEC, TLC, ESR and lymphocyte count were apparently higher in close than open pyometra and correlated with clinical signs. These findings were of prognostic value in diagnosing canine pyometra.